Patterns of multiple intelligence and its relationship to the degree of possession of problem-solving skill among fourth-grade students in the Syrian city of Hama - Alomary, Mai; Farha, Fatima; Shaaban, Amna (Journal of Curriculum and Teaching Methodology, 2022)
The current study aimed to identify the patterns of multiple intelligence among fourth-grade students in the city of Hama, and to identify the relationship between the type of intelligence (linguistic, logical, visual, kinesthetic, musical, personal, and social) and the degree to which students possess problem-solving skill. The study adopted the descriptive analytical approach. The study adopted the multiple intelligences scale of the researcher Hatem Al-Busais, which was codified on the Syrian environment. The study was applied to (376) male and female students of the fourth grade.The study showed that:- The level of multiple intelligences came to a medium degree, and that the most common intelligence among fourth-grade students is linguistic intelligence with a high degree, arithmetic mean (3.84) and standard deviation (0.89), followed by logical intelligence with a high degree, arithmetic mean (3.25) and standard deviation (1.110), then intelligence Visual with a medium degree, arithmetic mean (2.51), and standard deviation (1.115),  then kinesthetic intelligence with a medium degree, arithmetic mean (2.50) and standard deviation (1.120), Then the social intelligence with a medium degree and an arithmetic mean (2.49) and a standard deviation (1.149), followed by a musical intelligence with a low degree and an arithmetic mean (2.22), and a standard deviation (1.090), and finally personal intelligence with a low degree and an arithmetic mean (1.76) and a standard deviation (1.067), as it turned out.- There is a relationship between intelligence (logical, social), and the degree of problem-solving skill, while we note that there is no relationship between the degree of problem-solving skill, and intelligence (linguistic - kinesthetic - visual - musical - personal).
Keywords: multiple intelligences; problem-solving skills; fourth grade students